Lemmus amurensis Vinogradov 1924 ... - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Amur Lemming Lemmus amurensis Vinogradov, 1924 Type locality: Near Pikan [River mouth] on Zeya River, Amursk Oblast [cytb sequence of the holotype: KX455628] (Baranova & Gromov 2003; Abramson & Petrova 2018). Synonyms: Not available. Distribution: East Siberian mountain species with a restricted range: Transbaikalia, South Yakutia, and the Upper Amur Basin (Abramson & Petrova 2018). Comments: The taxonomy and distribution of this species was clarified recently based on DNA sequence data (Abramson & Petrova 2018). ... : Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on pages 115-116, DOI: 10.37828/em.2021.40.8, http://zenodo.org/record/13233031 ...